Advances in Universal CAR-T Cell Therapy - Lin, Haolong; Cheng, Jiali; Mu, Wei; Zhou, Jianfeng; Zhu, Li (Frontiers in Immunology, 2021)
Chimeric antigen receptor T (CAR-T) cell therapy achieved extraordinary achievements results in anti-tumor treatments, especially against hematological malignancies, where it leads to remarkable, long-term antineoplastic effects with higher target specificity. Nevertheless, some limitations persist in autologous CAR-T cell therapy, such as high costs, long manufacturing periods, and restricted cell sources. The development of a universal CAR-T (UCAR-T) cell therapy approach is an attractive breakthrough point that may overcome most of these drawbacks. Here we review the progress and challenges in CAR-T cell therapy, especially focusing on comprehensive comparison in UCAR-T cell therapy to original CAR-T cell therapy. Furthermore, we summarize the developments and concerns about the safety and efficiency of UCAR-T cell therapy. Finally, we address other immune cells, which might be promising candidates as a complement for UCAR-T cells. Through a detailed overview, we describe the current landscape and explore the prospect of UCAR-T cell therapy.